PENYELESAIAN SENGKETA PERDATA MELALUI MEDIASI DI KELURAHAN TOMBOLO KECAMATAN SOMBA OPU - Adis Nevi Yuliani Adis; Ayu Chairun Nisa Ayu Chairun Nisa; Djulya Eka Pusvita Djulya Eka Pusvita; Murdiono Murdiono; Arini Asriyani Arini Asriyani; Widhy Andrian Pratama Widhy; Halimah Endang Widyaningsih (P3M Sekolah Tinggi Agama Islam Miftahul Ulum, 2025)
Mediation helps to rebuild trust, improve communication, and restore relationships that have been damaged by conflict. Research shows that mediation can provide significant improvements in employment relationships, reduce levels of conflict in the workplace, and contribute to increased productivity. The official implementation of mediation is rooted in social dynamics that reflect public dissatisfaction with the performance of the judiciary, which has so far acted as the only institution for resolving disputes. The implementation of Community Service (PKM) is an integral part of the implementation of the Tridharma of Higher Education carried out by lecturers from the Law Department, Faculty of Law, Syekh Yusuf Al-Makassari University, Gowa. This activity aims to provide real contributions through the provision of legal services in the form of legal assistance and assistance in order to provide direct benefits and have a positive impact on the community. This activity took place on Thursday, April 17, 2025, at Jalan, Paccalayya No. 1 Lingkungan Pa'bangiang, Gowa Regency, South Sulawesi. The main focus of this PKM activity is to provide direct legal assistance to people in need. From the results and outputs of community service, it can be concluded that legal mediation is a method of dispute resolution involving a neutral mediator and the disputing parties. This process emphasizes a collaborative approach and reduces hostility. The success of legal mediation is highly dependent on its ability to facilitate effective communication, create open dialogue space, and formulate solutions that are mutually acceptable to all parties involved